The Theological Orientation of Francisco Suárez’s Metaphysics - Salas, Víctor M. (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
The common narrative concerning the metaphysics of Francisco Suárez among a diverse number of thinkers is that the Jesuit presents an «indifferent» ontology that neglects the traditional medieval conception of God as utterly transcendent and unique. Though the critiques leveled against Suárez are legion and equally as diverse as the critics from whom they derive, as I see it, there is a common, albeit unexpressed, conviction that the Jesuit’s thought ultimately results in the secularization of metaphysics. By «secularization» I mean that, as frequently asserted, Suárez’s analysis of the nature of being transpires entirely without the need for adverting to any overarching theological framework. In this essay, I challenge that view and argue that Suárez’s metaphysics is thoroughly determined by his theological vision and project.
Keywords: metaphysics; theology; analogy of being; secularity